2011
DOI: 10.3945/ajcn.110.009357
|View full text |Cite
|
Sign up to set email alerts
|

Omega-3 fatty acids and incident type 2 diabetes: the Singapore Chinese Health Study

Abstract: Consumption of nonmarine sources (ALA) of omega-3 FAs is associated with a decreased risk of type 2 diabetes in Chinese Singaporeans.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
79
1
5

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 96 publications
(88 citation statements)
references
References 42 publications
3
79
1
5
Order By: Relevance
“…Flaxseed oil had no impact on fasting blood serum glucose, insulin or HbA1c levels. It is concluded that high doses of flaxseed oil have no effect on glycemic control in type 2 diabetics (Brostow et al, 2011).…”
Section: Flaxseed Oil For Pre-diabeticsmentioning
confidence: 95%
See 2 more Smart Citations
“…Flaxseed oil had no impact on fasting blood serum glucose, insulin or HbA1c levels. It is concluded that high doses of flaxseed oil have no effect on glycemic control in type 2 diabetics (Brostow et al, 2011).…”
Section: Flaxseed Oil For Pre-diabeticsmentioning
confidence: 95%
“…In the Singapore, Chinese Health Study conducted by Brostow et al (2011) examined the association between total omega-3 FAs, marine omega-3 (EPA, DHA), nonmarine omega-3 (ALA) and omega-6 (n-6) FAs and omega-6: omega-3 ratio on risk of type 2 diabetes in a Chinese population of Singapore. The analysis included 43,176 Chinese men and women free of chronic disease, aged 45-74 year.…”
Section: Flaxseed Oil For Type 2 Diabeticsmentioning
confidence: 99%
See 1 more Smart Citation
“…It may be that the chemicals in fish can explain these inconsistencies. A study shows that plant-based omega 3s have different effects than marine-based omega 3s in relation to type 2 diabetes [22], it was opined that this may be possibly due to the contaminants present in fish.…”
Section: Chemicals and Omega-3smentioning
confidence: 99%
“…n-3 LC-PUFA have been shown to reduce the incidence of cardiovascular diseases [1][2][3][4][5][6]. Emerging evidence also suggests a protective effect against type-2 diabetes [7], and an improvement of the muscle protein synthesis rate in older adults with the consumption of n-3 LC-PUFA [8]. The level of n-3 LC-PUFA in the circulation has been shown to correlate with CVD risk [5] and regular consumption of n-3 LC-PUFA is a recognized strategy to decrease CVD risk factors.…”
mentioning
confidence: 99%